PENERAPAN MEDIA PEMBELAJARAN INTERAKTIF BERBASIS WORDWALL UNTUK MENINGKATKAN KEAKTIFAN BELAJAR SISWA DI SD NEGERI 064024 MEDAN SELAYANG - Regina Sipayung; Br Sihaloho, Angel; Erlina Hutagalung; Triani Br Sagala; Sri Lasmida Ito Marbun; Devi Simbolon; Enjelika Megawati Simanjuntak; Meilanye Claudia; Maria Uli Tamba; Erwin Gamaliel Napitupulu (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aimed to determine the implementation of Wordwall-based interactive learning media in improving the learning activeness of fourth-grade students in Natural and Social Sciences (IPAS) at SD Negeri 064024 Medan Selayang. The study employed a Classroom Action Research (CAR) design using the Kemmis and McTaggart model, which consisted of planning, action, observation, and reflection stages. The research participants were 20 fourth-grade students. Data were collected through classroom observations using a learning activeness observation sheet that assessed students' attention to learning materials, willingness to ask questions, ability to answer questions, and participation during classroom activities. The collected data were analyzed using descriptive quantitative analysis based on the percentage of students' learning activeness. The findings revealed that the implementation of Wordwall-based interactive learning media successfully improved students' learning activeness. The average learning activeness increased from 57.45% before the implementation of Wordwall to 81.95% after its implementation, with an average improvement of 25%. Furthermore, all students demonstrated increased participation throughout the learning process. The use of Wordwall created a more interactive, engaging, and enjoyable learning environment that encouraged students to participate actively in classroom activities. Therefore, Wordwall-based interactive learning media can be considered an effective alternative for enhancing students' learning activeness in IPAS learning at the elementary school level.